Beyond Neutralizing Antibody Levels: The Epitope Specificity of Antibodies Induced by National Institutes of Health Monovalent Dengue Virus Vaccines - Swanstrom, Jesica A (J Infect Dis, 2019)
BACKGROUND: Dengue virus is an emerging mosquito-borne flavivirus responsible for considerable morbidity and mortality worldwide. The Division of Intramural Research, National Institute of Allergy and Infectious Diseases of the US National Institutes of Health (NIH) has developed live attenuated vaccines to each of the 4 serotypes of dengue virus (DENV1–4). While overall levels of DENV neutralizing antibodies (nAbs) in humans have been correlated with protection, these correlations vary depending on DENV serotype, prevaccination immunostatus, age, and study site. By combining both the level and molecular specificity of nAbs to each serotype, it may be possible to develop more robust correlates that predict long-term outcome. METHODS: Using depletions and recombinant chimeric epitope transplant DENVs, we evaluate the molecular specificity and mapped specific epitopes and antigenic regions targeted by vaccine-induced nAbs in volunteers who received the NIH monovalent vaccines against each DENV serotype. RESULTS: After monovalent vaccination, subjects developed high levels of nAbs that mainly targeted epitopes that are unique (type-specific) to each DENV serotype. The DENV1, 2, and 4 monovalent vaccines induced type-specific nAbs directed to quaternary structure envelope epitopes known to be targets of strongly neutralizing antibodies induced by wild-type DENV infections. CONCLUSIONS: Our results reported here on the molecular specificity of NIH vaccine–induced antibodies enable new strategies, beyond the absolute levels of nAbs, for determining correlates and mechanisms of protective immunity.